Pemenuhan Hak Anak Hasil Perkawinan Siri Perspektif Hukum Positif Dan Hukum Islam - Haslinda Jumadi; Rifdan Rifdan; Mustaring Mustaring (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2023)
Abstract: (1) The purpose of this research is to determine, in accordance with Article 55 of the Marriage Law Number 1 of 1974, the legal status of children born to multiple marriages. 2) Under the Marriage Law, rights to child custody and inheritance in multiple marriages. Researchers use methods like documentation, observation, and interviews to gather data for this purpose. Qualitative descriptive analysis is used to process the research results' data. According to article 55 of Law Number 1 of 1974, the legal position of children in serial marriages reveals that the serial marriages that occur in their field do not register their marriages, leaving the positive law of their children's legal position uncertain and their rights as children unrecognized. According to Islamic law, Siri marriage does not violate the pillars and conditions of the child being born legally but siri marriage caused by being pregnant outside of marriage has many differences of opinion, one of which is that the status of the child is legal if the child is born within 6 months or 180 days of the marriage contract of both parents while the child born in the provision is considered a child outside the marriage which is only to the mother. (2) According to Article 186 of the Compilation of Islamic Law, a child born without a marriage only has a relationship that is mutually inherited with his mother and her family. However, the proof of the legal relationship of the child resulting from the marriage did not cause him to be able to inherit from his biological father (although it is technologically provable). This opinion was also corroborated by a Fatwa from the Indonesian Ulema Council dated March 10, 2012 which stated that the child was only entitled to a mandatory will. (3) With regard to the custody of a child outside of marriage if the child is born before 6 months, the child is only related to his mother through marriage or kinship, whereas a child born after six months is considered a legal member of the father and mother's family.